Economic evaluation of point-of-care testing in the remote primary health care setting of Australia’s Northern Territory - Spaeth BA; Kaambwa B; Shephard MDS; Omond R (Dove Medical Press, 2018)
Brooke A Spaeth,1 Billingsley Kaambwa,2 Mark DS Shephard,1 Rodney Omond3 1Flinders University International Centre for Point-of-Care Testing, Flinders University, Adelaide, SA, Australia; 2Health Economics Unit, College of Medicine and Public Health, Flinders University, Adelaide, SA, Australia; 3Primary Health Care Branch, Top End Health Service, Department of Health, Northern Territory Government, Darwin, NT, Australia Aim: To determine the cost-effectiveness of utilizing point-of-care testing (POCT) on the Abbott i-STAT device as a support tool to aid decisions regarding the emergency medical retrievals of patients at remote health centers in the Northern Territory (NT) of Australia.Methods: A decision analytic simulation model–based economic evaluation was conducted using data from patients presenting with three common acute conditions (chest pain, chronic renal failure due to missed dialysis session(s), and acute diarrhea) at six remote NT health centers from July to December 2015. The specific outcomes measured in this study were the number of unnecessary emergency medical retrieval prevented through POCT. Cost savings through prevented unnecessary medical retrievals for each presentation type were then determined and extrapolated to give per annum NT-wide estimates.Results: POCT prevented 60 unnecessary medical evacuations from a total of 200 patient cases meeting the selection criteria (48/147 for chest pain, 10/28 for missed dialysis, and 2/25 for acute diarrhea). The associated cost savings were AUD $4,674, $8,034, and $786 per patient translating to NT-wide savings of AUD $13.72 million, $6.45 million, and $1.57 million per annum (AUD $21.75 million in total) for chest pain, missed dialysis, and acute diarrhea presentations, respectively.Conclusion: This study demonstrated that POCT when used to aid decision making for acutely ill patients delivered significant cost savings for the NT health care system by preventing unnecessary emergency medical retrievals. Keywords: acute, remote health, primary care, retrieval, acute care, myocardial infarction, dialysis, dehydration, indigenous health, pathology testing, medical retrieval, cost-effectiveness